Maternity leave versus early childcare – What are the long-term consequences for children? - Nabanita Datta Gupta; Jonas Jessen (IZA World of Labor, 2023)
There is growing agreement among parents in high-income countries that having a working mother does not harm a preschool child. Yet, research is ongoing on what the long-term effects on children are of being looked after at home (primarily by their mothers) or in childcare. Most studies find positive effects of childcare on child outcomes for children from disadvantaged backgrounds and moderate effects for children from more advantaged backgrounds. Policymakers need to improve compensation and the working environment for the sector if a high quality level is to be achieved and if the beneficial effects are to be maintained.
Keywords: J13; 330; publicly subsidized child care; maternity leave schemes; long-term outcomes